Summer annual silages and hay for growing steers - Bolsen, K.; Ilg, H.; Axe, D.; Thompson, W. (Kansas State University. Agricultural Experiment Station, 2011)
Sudangrass, pearl millet, sorghum-sudangrass, and forage sorghum silages and sorghum-sudan hay were full-fed to yearling steers in a 90-day trial. Forage sorghum was harvested in the dough stage; the other four forages, in the late-vegetative stage. Steers consumed an average of 12.5% more hay than silage the first 42 days; hay feeding was discontinued then for lack of supply. At 90 days, steers fed forage sorghum silage out-performed those fed the other three silages. Compared with forage sorghum, the other silages had relative feeding values (based on rate and efficiency of gains) of 75% for sudangrass , 62% for pearl millet, and 68% for sorghum-sudan.
Keywords: Beef; Silage; Hay; Growing steers